Ageing in Advanced Industrial States Riding the Age Waves - Volume 3 - Tuljapurkar, Shripad.; Ogawa, Naohiro.; Gauthier, Anne H. (International Studies in Population ;, 2010)
Population growth slowed across the world in the last decades of the 20th century, changing substantially our view of the future. The 21st century is likely to see the end to world population growth and become the century of population aging, marked by low fertility and ever-increasing life expectancy. These trends have prompted many to predict a gloomy future caused by an unprecedented economic burden of population aging. In response, industrialized nations will need to implement effective social and economic policies and programs. This is the final volume in a series of three. The papers included explore many examples and strengthen the basis for effective economic and social policies by investigating the economic, social, and demographic consequences of the transformations in the structures of population and family. These consequences include changes in economic behavior, both in labor and financial markets, and with regard to saving and consumption, and intergenerational transfers of money and care.